Chromosomal Changes in relation to Clinical Outcome in Larynx and Pharynx Squamous Cell Carcinoma - Mario Hermsen; Marta Alonso Guervós; Gerrit Meijer; Paul van Diest; Carlos Suárez Nieto; Cesar Alvarez Marcos; Andrés Sampedro (Cellular Oncology)
Invasive head and neck squamous carcinomas are among the cytogenetically most complex tumors. Perhaps for this reason, there is little consensus on the prognostic value of specific chromosomal aberrations. Here we present Results of CGH analysis of 56 clinically well-characterized set of head and neck cancers, consisting of larynx and pharynx only. The aim was to find possible associations with clinical outcome. The major chromosome arms showing gains were (in decreasing order): 3q, 7q, 8q, 5p, 11q13, 17q and 18p, and losses occurred at 3p, 11qter, 4p, 18q, and 5q. The segments most frequently amplified were 3q26-qter, 11q13, 11q22, 3q12–13, 18p11.3, 18q11.2 and 8q24.3. Tumors with stages III and IV, and lymph node positive tumors had a worse clinical outcome. Surprisingly, no specific chromosomal abnormality correlated with disease-free survival. The only aberration that correlated to one of the clinico-pathological parameters was amplification 11q13, that occurred solely in lymph node positive, stage IV tumors. However 11q13 amplification did not correlate with disease-free survival. These Results seem to indicate that genetic alterations at the level of chromosomes have limited prognostic value in patients with invasive larynx and pharynx squamous cell carcinomas.